2016
DOI: 10.1111/jmwh.12409
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behavior, Satisfaction, and Contraceptive Use Among Postpartum Women

Abstract: By 6 weeks postpartum, 4 in 10 women had resumed vaginal intercourse, with only half using contraception. Counseling regarding postpartum contraception should meet normative behavior. Thus, contraceptive plans need to be established during prenatal care, and the postpartum visit should occur earlier than the current standard time of 6 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
27
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 34 publications
8
27
1
2
Order By: Relevance
“…Approximately half of the participants (49%) in this study resumed vaginal intercourse by weeks 6-8 postpartum, which is in line with corresponding figures in the literature (41-61%) [6,[14][15][16]. Generally, women in our study appeared to be highly motivated to initiate contraceptive use by weeks 6-8, since 91.5% were using some contraceptive method.…”
Section: Findings and Interpretationsupporting
confidence: 90%
See 1 more Smart Citation
“…Approximately half of the participants (49%) in this study resumed vaginal intercourse by weeks 6-8 postpartum, which is in line with corresponding figures in the literature (41-61%) [6,[14][15][16]. Generally, women in our study appeared to be highly motivated to initiate contraceptive use by weeks 6-8, since 91.5% were using some contraceptive method.…”
Section: Findings and Interpretationsupporting
confidence: 90%
“…In the adjusted analyses, previous use of an effective contraceptive method and the return of the menstrual cycle played a central role in leading to use of the previous effective method, which is a finding supported by other authors [14,28]. Paradoxically, the intentional use of LAM despite high awareness of its limitations may be due to its convenience and to financial reasons.…”
Section: Findings and Interpretationsupporting
confidence: 52%
“…This seems to be normal as two out of every three women experience dyspareunia when resuming intercourse. [46] The prevailing evidence suggests women can resume intercourse about six to eight weeks after childbirth [44,46,58,93]; however other studies [43,94] reported sexual activities other than intercourse can be resumed as early as one to two weeks. The women in this study believe they needed more time to return to intercourse, but they did not try other types of sexual activity, such as masturbation or oral sex.…”
Section: Discussionmentioning
confidence: 99%
“…As recommended by Pauleta et al [45], women need to be able to speak openly with their clinician about their sexual health and to be clearly informed about the changes they should expect. Since consultations are usually more frequent in the antenatal than the postpartum period [93], there might be less time available during the postpartum visits to address sexual health. Similar to other reports [60], the women noted their care was always focused on the baby, and not them during the postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…In their study of postpartum sex and contraception use, Sok et al found that 43% of women had resumed intercourse by 6 weeks postpartum but only 49% were using contraception. Changes in sexual behavior were common; most notably, women gave and received oral sex less frequently than they did before and during pregnancy.…”
mentioning
confidence: 99%